FFR-based radio resource allocation for RIS-aided D2D communication in multicell cellular network - Misfa Susanto; Soraida Sabella; Helmy Fitriawan; Ayu Purwarianti; Azrina Abd Aziz (Institute of Advanced Engineering and Science, 2026)
Device-to-device (D2D) communication and reconfigurable intelligent surfaces (RISs) are two technologies that are attractive components of future wireless networks. D2D allows nearby devices to communicate directly, which helps boost network efficiency by reducing the load on base stations. However, since D2D often uses the same frequency bands as regular cellular users, it can cause interferences. RIS, on the other hand, enhances signal coverage by intelligently reflecting signals toward their intended destinations, but it can also unintentionally reflect interfering signals, especially in crowded multicell networks during downlink transmission. To address these interference challenges, this paper explores the application of a fractional frequency reuse (FFR) strategy purposed for networks that integrate both D2D and RIS technologies in multicell cellular network scenarios. The simulation outcomes imply that the proposed FFR method notably expands performances i.e., raising the signal quality in term of signal-to-interference-plus-noise-ratio (SINR) from 0.47 dB to 1.93 dB, enhancing throughput from 10.8 Mbps to 13 Mbps, and improving the bit error rate (BER) to 21 errors per 100 bits, demonstrating its effectiveness in improving network reliability and efficiency.